Leaving Poppy - Cann, Kate. (London : Scholastic, 2012)
Amber's family think she's gone to Cornwall on holiday, but really she's left home. She's forging a new life - new housemates, new job and (with a little luck) new boyfriend. She feels bad because her mother and Poppy need her, but she's got to make the break, get out of their clutches... Then Amber falls ill and her family come to look after her. Something in the house responds to Poppy's presence, something malign and threatening. When Poppy moves into the attic, it gets even stronger, until evil seems to permeate everywhere and Amber thinks she might never be able to escape..
Young Adult.
Young Adult
Keywords: Ghost stories